A new species of Hannemania Oudemans, 1911 (Trombidiformes: Leeuwenhoekiidae) from Brazil - Bassini-Silva, Ricardo; Huang-Bastos, Matheus; Morais, Drausio Honorio; Alcantara, Edna Paulino [UNESP]; Ávila, Robson Waldemar; Welbourn, Cal; Ochoa, Ron; Barros-Battesti, Darci Moraes [UNESP]; Jacinavicius, Fernando de Castro (Taylor & Francis, 2021)
Hannemania has 27 described species parasitizing amphibians in the Americas. To date, five species have been recorded from Brazil. Here, we describe a new species for the country, collected parasitising the South American white-lipped grass frog, Miranda’s white-lipped frog, basin white-lipped, Bahia dwarf frog and granular toad all from Ceará state, Brazil. http://www.zoobank.org/urn:lsid:zoobank.org:pub:CD88F94F-ED46-4BA9-8E8E-B4AA1D2815B1.
Keywords: amphibia; Ceará state; Chigger mites; ectoparasites; frogs; South America